Association of COVID-19 vaccination prioritization and hospitalization among older Washingtonians - Lavista Ferres, Juan M.; Richardson, Barbra A.; Weeks, Bill (Journal of the American Geriatrics Society, 2021)
In experimental conditions, all Food and Drug Administration-approved vaccines have demonstrated vaccine-related reductions in COVID-19 hospitalizations.1, 2 While the literature is rapidly evolving, several observational studies have evaluated the efficacy of COVID-19 vaccination on particular populations. Studies of healthcare workers in Jerusalem,3 Italy,4 and the United States found reduced COVID-19 infection rates soon (generally within 1–2 weeks)5 following vaccination. National observational studies of the general population in Scotland6 and Israel7 found lower rates of symptomatic infection, hospitalization, and death soon (within 2–3 weeks) following vaccination.Starting January 18, 2021, Washington prioritized Washingtonians aged 65 and older (65+) for COVID-19 vaccination.8 We sought to explore whether reduced COVID-19 hospitalizations could be discerned in real-world conditions following vaccination prioritization for that population. To do this, we used historical trends of Washington State COVID-19 hospitalizations for the 65+ and other age groups to generate estimates of COVID-19 hospitalization in the 65+ years age group had prioritization not occurred, and compared these estimates with actual hospitalization in the first 6 weeks following prioritization.